The role of dislodgement in the territorial ecology of the owl limpet, Lottia gigantea. Issue 4 (3rd July 2020) - Kabala, Ryan T.; Swinford, Natalie A.; Mason, Maria J.; Wright, William G.
Abstract : Ascertaining the risks and benefits of different behaviors is a central goal of research on territoriality. Although most territorial behavior is ritualized, with concomitant reduced risks for both residents and intruders, this ritualization is generally found to be underpinned by rare, highly consequential, interactions. The agonistic behavior of the intertidal owl limpet, Lottia gigantea, involves defense of a feeding territory, and includes a relatively explosive thrusting response by territory holders against intruding conspecifics. We here ask whether this thrusting behavior is capable of entirely dislodging intruders from their rocky wave-swept substratum, thereby ridding the resident of future challenges by that intruder. Our field measurements of the strength of territorial thrusts, as well as thrust resistance, indicate that territorial limpets are strong enough to overcome the resistance of small to medium sized (<40 mm) conspecifics encountered on their territories. Interestingly, at least 44% of the limpets dislodged from the rock substratum during a retreat or territorial response survived in a new location. Growth of these survivors was at least as rapid as that of undisturbed limpets in the old location. We conclude that shell thrusting during the territorial response of Lottia gigantea can reduce the cost of territorial defense by dislodging smaller conspecifics, thereby eliminating them from all future interactions. Conversely, the risk incurred by these smaller conspecifics while intruding onto territories of larger individuals is likely mitigated by the surprisingly high survival rate, and subsequent normal growth, of dislodged limpets.